Complex regional pain syndrome: intradermal injection of phenylephrine evokes pain and hyperalgesia in a subgroup of patients with upregulated α1-adrenoceptors on dermal nerves. Issue 11 (November 2018) - Drummond, Peter D.; Morellini, Natalie; Finch, Philip M.; Birklein, Frank; Knudsen, Lone F.
Abstract : Abstract: The aim of this study was to determine whether upregulated cutaneous expression of α1 -adrenoceptors (α1 -AR) is a source of pain in patients with complex regional pain syndrome (CRPS). Immunohistochemistry was used to identify α1 -AR on nerve fibres and other targets in the affected and contralateral skin of 90 patients, and in skin samples from 38 pain-free controls. The distribution of α1 -AR was compared between patients and controls, and among subgroups of patients defined by CRPS duration, limb temperature asymmetry, and diagnostic subtype (CRPS I vs CRPS II). In addition, α1 -AR expression was investigated in relation to pain and pinprick hyperalgesia evoked by intradermal injection of the α1 -AR agonist phenylephrine. Expression of α1 -AR on nerve bundles in the CRPS-affected limb was greater in patients who reported prolonged pain and pinprick hyperalgesia around the phenylephrine injection site than in patients with transient pain after the injection. In addition, α1 -AR expression in nerve bundles was greater in patients with CRPS II than CRPS I, and was greater in acute than more long-standing CRPS. Although less clearly associated with the nociceptive effects of phenylephrine, α1 -AR expression was greater on dermal nerve fibres in the painful than contralateral limb. Together, these findings are consistent with nociceptive involvement of cutaneous α1 -AR in CRPS. This involvement may be greater in acute than chronic CRPS, and in CRPS II than CRPS I. Abstract : Supplemental Digital Content is Available in the Text.Intradermal injection of phenylephrine evoked prolonged pain and pinprick hyperalgesia in CRPS patients with histochemical signs of α1 -adrenoceptor upregulation in dermal nerve bundles.